Molecular classification for some species of ground beetles to the Carabidae family spread in Diyala Governorate (Texas Journal of Agriculture and Biological Sciences, 2022)
The existence of millions of species for living organisms and the different stages of their life transformation made the classification of the animal kingdom very difficult, Insects are considered the most numerous in animals and their classification depends primarily on phenotypic traits. In recent years, molecular methods have been adopted to distinguish between species and genera of common descent that have not been distinguished by phenotypic methods. In the past ten decades, molecular methods, especially mitochondrial and nuclear DNA sequence data, have been used to classify insect species and genera of common descent. This study aims to use the technique of random polymerase chain reaction with the presence of ten random primers to distinguish among Distichus planus, Harpalus rufipes, Chlaenius nigricornis and Brachinus bayardi, the results showed that the total number of bundles is 36 and the number of polymorphic bundles is 32 for all ten primers. Primers OP-A04, OP-A08, OP-C06, OP-C10 and OP-C18 showed the highest percentage of polymorphism which is 100%, while primer OP-C15 showed the lowest percentage of polymorphism which is 60%, while primers OP-A15 and OP -B09 and OP-B14 No bundle appeared, so the polymorphism percentage was 0%. In addition, the highest percentage of primer efficiency was 25% at OP-A04 and the lowest percentage was 5.55 at OP-A08. Finally, the primer enabled OP-A04 was able to distinguish between the Distichus planus, Harpalus rufipes, Chlaenius nigricornis and Brachinus bayardi where the discriminating ability was 28.125%, while the primers OP-A15, OP-B09 and OP-B14 were not able to distinguish between the four types because of their discriminatory ability was 0%.